Graph-based algorithms for the efficient solution of optimization problems involving monotone functions - Consolini, Luca; Laurini, Mattia; Locatelli, Marco (Computational optimization and applications, 2019)
In this paper, we address a class of specially structured problems that include speed planning, for mobile robots and robotic manipulators, and dynamic programming. We develop two new numerical procedures, that apply to the general case and to the linear subcase. With numerical experiments, in the linear case we show that the proposed algorithms outperform generic commercial solvers.